Saliva cortisol, physical exercise and training: influences of swimming and handball on cortisol concentrations in women - Filaire, E.; Duche, P.; Lac, G.; Robert, A. (European Journal of Applied Physiology, 1996)
The aim of this study was to observe the influence of physical exercise and training on saliva cortisol concentrations in women. Three groups of adult women were studied: one group of sedentary controls (n = 7) and two groups of sportswomen who competed in either handball (n = 14) or swimming (n = 10) at a national level. These sportswomen gave six saliva samples during a day that included exercise which was part of their annual training programme. We noticed a significant increase in saliva cortisol concentration after exercise in the handball players (6 p.m. vs 7.30 p.m. P < 0.05) which did not appear in the swimmers or the sedentary group. There was no difference between the sedentary group and the swimmers for each sample of the day. These results showed that the type of sport played seemed to influence the concentration of saliva cortisol, the type of stress involved, the respective haemodynamic conditions of swimming and running and thermal stress also playing a part. Moreover, it seemed that the level of performance influenced the secretion of cortisol in the saliva.